2002
DOI: 10.1159/000064266
|View full text |Cite
|
Sign up to set email alerts
|

Blut- und Gewebseosinophilie, Mistellektin-Antikörper und Lebensqualität bei einer Mammakarzinom-Patientin unter intratumoraler und subkutaner Misteltherapie

Abstract: Blood and Tissue Eosinophilia, Mistletoe Lectin Antibodies and Quality of Life in a Breast Cancer Patient Undergoing Intratumoral and Subcutaneous Mistletoe Injection Background: Mistletoe therapy (MT) is a method of complementary medicine whose efficacy is controversially discussed. Until now there is a lack of data of high-dose intratumoral application. Patient and Methods: We are presenting a 3-year follow-up of an 80-year-old woman with metastasized breast cancer (c2T3/N1/M1) receiving combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…VA-applications are usually well tolerated and had only few and mild side-effects [ 23 25 ]. Various reports support clinical findings that VA-therapy can improve and stabilize HRQL in cancer patients, especially in breast cancer during CTX [ 26 29 ]. In this noninterventional, observational study, the ICS was used to evaluate the effects of add-on VA-therapy on the internal coherence in breast cancer patients with the advice for CTX.…”
Section: Introductionmentioning
confidence: 68%
“…VA-applications are usually well tolerated and had only few and mild side-effects [ 23 25 ]. Various reports support clinical findings that VA-therapy can improve and stabilize HRQL in cancer patients, especially in breast cancer during CTX [ 26 29 ]. In this noninterventional, observational study, the ICS was used to evaluate the effects of add-on VA-therapy on the internal coherence in breast cancer patients with the advice for CTX.…”
Section: Introductionmentioning
confidence: 68%
“…The authors found sufficient evidence to recommend the use of Iscador for treatment of cancer in breast cancer patients with or without axillary metastases. In 2002, Kröz et al [ 92 ] reported some benefits of mistletoe therapy in survival and tumor reduction in women with metastasized breast cancer. They applied combined intra-, peritumoral, and subcutaneous abnoba-Viscum(r) with concomitant pamitron acid to breast cancer patients.…”
Section: Clinical Studiesmentioning
confidence: 99%